PENGARUH APPLICATION MOBILE MINDFULNESS (MM) TERHADAP TINGKAT STRESS PADA MAHASISWA DI TANGERANG RAYA - Faridah, Ida; Afiyanti, Yati; Fatonah, Siti (Nusantara Hasana Journal, 2022)
Stress can be defined as an excessive pressure experienced by individuals. The number of students who experience stress is caused by several factors including academic stress, a lot of assignments and busy class scheduls. Because of this, the researceher provides an intervension, namely an application-based meditation called â€œMobile Maindfulness (MM)â€ in the hope that this intervention can reduce stress levels. Experienced by students. This research uses a pre-experimental quantitative method approachwhit aresearch design of One Group Pretest-Posttest Design. The number of sampels in this study were 112 respondents with purposive sampling. From the results of the Paried Simple T Test before and after the intervension was given, the was adifference between the pre-test and post-test with P value < 0.05. There are there is a significant effect between teh use of the Mobile Maindfulness MM Application on Stress Level in Students in Tangerang Raya.